POTENSI MALADMINISTRASI TERHADAP PELAYANAN VAKSINASI COVID-19 - Triani, Ni Putu Erna Ayu; Sudiarta, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol 11 No 2 (2023)DO - 10.24843/KS.2023.v11.i02.p06, 2023)
Penulisan artikel ini bertujuan yaitu untuk mengkaji regulasi berkaitan dengan pelaksanaan penanganan Vaksinasi COVID-19 dari perspektif Hukum Administrasi Negara serta untuk mengetahui potensi terjadinya maladministrasi dalam regulasi pelaksanaan Vaksinasi COVID-19. Penulisan artikel ini mempergunakan metode penulisan yuridis normatif dengan mengkaji bahan hukum kepustakaan serta menggunakan pendekatan perundang-undangaan. Hasil studi ini menunjukan adanya pertama, penataan regulasi vaksinasi COVID-19 melalui Peraturan Menteri Kesehatan Nomor 10 Tahun 2021 yang mengatur dan menetapkan sasaran pelaksanaan vaksinasi COVID-19 yang merupakan masyarakat kelompok prioritas. Kedua, menunjukan adanya potensi maladministrasi dalam regulasi pelaksanaan Vaksinasi COVID-19 diantaranya: terdapat penyaluran vaksin COVID-19 yang tidak masuk dalam prioritas vaksinasi, dan kurangnya pemahaman terhadap tahapan vaksinasi yang telah ditentukan sebelumnya. The purpose of writing this article is to review regulations related to the handling of COVID-19 vaccination from the perspective of State Administrative Law and to find out the potential for maladministration in the regulation of the implementation of COVID-19 Vaccination. The writing of this article uses the normative juridical writing method by examining literature law materials and using a statutory approach. The results of this study show that first, the arrangement of the COVID-19 vaccination regulations through the Minister of Health Regulation Number 10 of 2021 which regulates and sets targets for the implementation of COVID-19 vaccination which is a priority group community. Second, it shows the potential for maladministration in the regulation of the implementation of COVID-19 Vaccination, including there is the distribution of the COVID-19 vaccine that is not included in the vaccination priority and a lack of understanding of the previously determined vaccination stages.